Assessment of Reverse Osmosis Water and Some Types of Packaged Bottled Water in Basra City, Southern Iraq - Al-Khafaji, Samar A.; Alawadi, Wisam A.; Altaee, Asaad M.R.; Maki, Anwar A.; Al-Shmailawi, Abdullah H. (Mesopotamian Journal of Marine Sciences, 2024)
Global sales of mineral water have increased considerably to reach a value of more than 35 billion US dollars, mainly due to public perceptions of its purity and safety, as well as public concerns about the quality of tap water. A total of 24 samples (12 reverse osmosis (RO) water samples taken from three regions and 12 samples of three brands of bottled water) were collected randomly. The samples were analyzed using the membrane filtration technique for their bacteriological quality (total and fecal coliforms per 100 mL). In addition, physiochemical analyses were undertaken to determine the dissolved oxygen, electrical conductivity, temperature, pH, total dissolved salts, turbidity, nitrate, calcium, magnesium, and chloride ions. Out of 12 RO water samples tested only 9 (75%) gave positive results for total coliforms, while 6 (50%) gave positive results for fecal coliforms. In contrast, 3 (25%) samples of bottled water gave positive test for total coliforms and 6 (50%) were positive for fecal coliforms. Both the RO and bottled water were contaminated with total and fecal coliforms, especially in hot months, and they reached unacceptable limits. Meanwhile, the physiochemical parameters were within acceptable limits, except in one sample, where the values of ions of calcium, magnesium, and chloride had been risen. According to the results obtained in this study, there should be a review of the water treatment process by water laboratories, especially in the summer, and there should be follow-ups by the inspection teams from the health and environment departments.